EVALUATION OF CARD AGGLUTINATION TEST/ Trypanosoma evansi IN EXPERIMENTALLY INDUCED INFECTION IN RABBIT (Journal of Veterinary Medicine and Animal Production, 2022)
This study was planned to evaluate the Card Agglutination Test for Trypanosomiasis (CATT). This technique was particularly developed for T. evansi. Eight locally bred rabbits were purchased from home-raised flocks. Six rabbits were inoculated on day 16 after purchase, by Trypanosome evansiisolate inter peritoneal (I/P) and 2 rabbits were left un inoculated as control. A direct Card Agglutination Test for detection of anti-trypanosome antibodies in serum or plasma of infected animals was used. The antigen consisted of cloned bloodstream form trypanosomes of RoTat 1.2 and a predominant variable antigen type (VAT) of T. evansi. The test was conducted in sera collected from eight different rabbits, taken during different stages of pre-infection, post-infection and after treatment with Cymelarsan. In pre-infection stage all rabbits were negative. Sera collected during infection stage was positive in all of inoculated rabbits, negative in un inoculated ones. Sera collected at 30 days after treatment showed variable results as some rabbits were positive for some time while others became negative. Death due to trypanosomiasis is usually a result of sever anaemia. In this study the Packed Cell Volume (PCV), HB & body weight of the infected rabbits were lower than that of the negative control. It was concluded that CATT is highly sensitive in antibody detection but the results should be carefully evaluated because antibodies can persist after treatment. The possible way is to consider the low PCV, haemoglobin (Hb) and antibody titer for evaluation of the infection situation.